The Crystal Structures of 2,5-Piperazinediones Having Epipolysulfide Bridges Between C3 and C6: The Structures of N,N′-Dimethyl-3,6-Epitetrathio-2,5-Piperazinedione - Davis, Betty R. (1973)
The crystal and molecular structure of N,N′-dimethyl-3,6-epitetrathio-2,5-piperazinedione (C(6)H(8)O(2)N(2)S(4)) has been determined from three-dimensional x-ray diffraction data collected by counter techniques. The substance crystallizes in the orthorhombic space group Fdd2, with a = 15.352(5), b = 20.432(7), and c = 6.635(2) Å; V = 2081.2(8) Å(3), D(meas) = 1.72(2) g/cm(3), and z = 8 molecules per unit cell. The molecule lies on a crystallographic 2-fold axis, the piperazinedione ring is in the boat conformation, and the deviation from planarity is 18°. The bonds of the tetrasulfide chain alternate in length so that the S-S distances are 2.0244(9), 2.076(1), and 2.0244(9) Å. The structural data were refined by least-squares methods to an R(F) of 2.5% by use of the 1089 independent reflections (2θ ≤ 71°; MoKα) for which F(0)(2) ≥ 3σ (F(0)(2)). Since this molecule is chemically identical with the active center of the recently isolated natural product sporidesmin G, our structural study constitutes a description of the epitetrathio-2,5-piperazinedione fragment of that molecule.